Functional Speech Styles And Their Characteristics - Narzullaeva Dilfuza Bafoevna; Bakhtiyarova Makhfirat Bakhadirovna (Peerian Journals Publishing, 2024)
This article is devoted to the study of functional styles of speech and their characteristics. Styles of speech are of great importance in linguistics, as they provide an overview of how to communicate effectively in various communicative situations. The article analyzes each of the main functional styles of speech - scientific, artistic, official, mass media and everyday styles. The specific lexical, grammatical and stylistic features of each style are shown, and their role in the social and cultural context is also discussed. The interaction of styles of speech and their role in modern communication are also discussed. It is expected that this article will help to understand speech more deeply and expand its functional capabilities.
Keywords: speech styles; lexical features; speech effectiveness; modern communication